Coexistence of anomalous muscle, persistent median artery, bifid median nerve causing carpal tunnel syndrome: A case report and literature review - Qin, Jun; Tan, Xia-xian; Xue, Ming-qiang; Wang, Jing-wei; Zhao, Jin-min; Sha, Ke (Frontiers in Pediatrics, 2023)
Carpal tunnel syndrome (CTS) is an upper extremity median nerve entrapment disorder that is rare in children and adolescents. Anatomical variations of the wrist, such as anomalous muscles, persistent median artery (PMA), and bifid median nerves (BMN), are rare etiology of CTS. Coexistence of all three variants combined with CTS in adolescents has been rarely reported. Case description: A 16-year-old right-hand dominant male presented to our clinic with several years of bilateral thenar muscle atrophy and weakness but no paresthesia or pain in his both hands. Ultrasonography showed that the right median nerve become significantly thinner, and the left median nerve was split into two branches by PMA. Magnetic resonance imaging (MRI) revealed that anomalous muscles in the bilateral wrist extending to the carpal tunnel, causing compression of the median nerve. Considering the possibility of CTS clinically, the patient underwent bilateral open carpal tunnel release without resection of anomalous muscles and PMA. The patient has no discomfort after 2 years. This suggests that anatomical variations of the carpal tunnel may contribute to CTS, which can be confirmed by preoperative ultrasonography and MRI, and the possibility of carpal tunnel anatomical variations should be considered when CTS occurs in adolescents. Open carpal tunnel release is an effective treatment for juvenile CTS without the need to resect abnormal muscle and PMA during the operation.